Dialektika Normatiitas Wahyu dan Realitas Sosial Dalam Pemikiran Hukum Munawir Sjadjali - Saifullah, Muhammad; Syarifuddin, Syarifuddin; Emzaed, Ali Murtadho; Aulia, Ajeng Hijriatul (Tazkir: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2025)
This study examines the dialectical relationship between the normativity of revelation and social reality in the Islamic legal thought of Munawir Sjadzali. Islamic law is not merely a normative-legal system derived textually from the Qur’an and Sunnah, but also an ethical framework that must be continuously interpreted in response to changing social conditions. Using a qualitative library research approach, this study critically analyzes Munawir Sjadzali’s major works to explore his epistemological framework, methodology of contextual ijtihad, and his contribution to the reactualization of Islamic law in modern Indonesia. The findings demonstrate that Munawir Sjadzali conceptualizes revelation as a source of moral objectives rather than rigid legal formulations, while social reality functions as the arena for the actualization of these objectives. His approach challenges legalistic and textualist paradigms that tend to absolutize historical formulations of fiqh without considering socio-historical transformations. Through his reinterpretation of issues such as Islamic inheritance law and banking interest, Munawir articulates a model of substantive justice grounded in maqāṣid al-sharī‘ah. However, this study also reveals critical tensions within his approach, particularly regarding methodological boundaries that prevent excessive relativism in legal interpretation. Overall, Munawir Sjadzali’s thought represents a significant intellectual contribution to the development of Islamic law as a dynamic, contextual, and justice-oriented system, offering a viable framework for reconciling divine normativity with the complexities of contemporary social life.